Lavengro: The Scholar, The Gypsy, The Priest - Borrow, George, 1803-1881; Sullivan, Edmund J. (Edmund Joseph), 1869-1933 (Salt Lake City, UT : Project Gutenberg, 2009)
"Lavengro: The Scholar, The Gypsy, The Priest" by George Borrow is a work published in 1851 that blends memoir and novel. Following a protagonist named George from his childhood in military barrack towns through various occupations$1 (Blawyer's apprentice, London hack writer, and traveling tinker$1 (Bthe book offers vivid portraits of Romany travelers and English low-life. Neither entirely autobiography nor pure fiction, this classic of 19th-century literature captures an era of strong, eccentric characters through episodes that interweave genuine experience with imaginative storytelling. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lavengro
Release date is 2009-12-28
Transcribed from the 1914 T. N. Foulis edition by David Price
Keywords: England -- Fiction; Romanies -- Fiction